The influence of intellectual capital on supply chain management of the Military Technical Institute - Savić Aleksandar O. (Savez inženjera i tehničara Srbije, 2021)
The Military Technical Institute (MTI), as the largest military scientific-research institution in the Ministry of Defense, mostly realizes its supply chain from the budget of the Republic of Serbia, while a smaller part is realized from its own revenues. The ongoing effort to improve its performance within the supply chain, but also the relevant role of human resources in MTI to manage their supply chain integration initiatives, uses an intellectual capital framework to analyze human, organizational and social capital in supply chain integration. In particular, it is proposed that intellectual or capital drive the integration of supply chains into MTI. The aim of this paper is to prove that intellectual capital influences the integration of processes and activities in supply chains in MTI.